METHODS AND TECHNIQUES COMBINATION WORKING BODIES OF COMPLEX SOIL PROCESSING MACHINES - VESELOVSKA, Nataliya; BURLAKA, Serhiy (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article establishes that the combination of working bodies in tillage machines can be optimized with the help of mathematical models and algorithms. These expressions provide valuable information about the performance of tillage machines and can be used to improve their efficiency and productivity. Using mathematical models and algorithms, engineers and inventors can optimize the design of tillage machines and improve their performance, leading to improved quality in field operations. In addition, the combination of working organs in tillage machines can also be analyzed using numerical simulation methods. These methods use mathematical models and algorithms to simulate the behavior of tillage machines in a virtual environment.Numerical modeling techniques provide valuable information about the behavior of tillage machines and their components, allowing engineers and designers to optimize their design and increase productivity. Using numerical simulation techniques, engineers and designers can verify the mathematical models and algorithms used in the analysis of tillage machines and improve their accuracy and reliability.Thus, the combination of working bodies in tillage machines can be analyzed and optimized with the help of mathematical models, algorithms and numerical modeling methods. These methods provide valuable information about the performance of tillage machines and can be used to improve their efficiency and productivity. Using these methods, engineers and designers can optimize the design of tillage machines and improve their performance, leading to increased efficiency and productivity in field operations. In addition, numerical modeling techniques can also be used to analyze the environmental impact of tillage. For example, modeling can be done to determine the impact of tillage on soil erosion and greenhouse gas emissions. By analyzing the results of this simulation, engineers and designers can improve the sustainability of tillage operations and reduce their environmental impact.
Keywords: soil; aggregate; model; tillage; mathematical model; indicators; soil tillage aggregate roller; cultivator; working bodies